Implementasi Program Penanganan Prasarana Dan Sarana Umum (PPSU) Di Kelurahan Melawai Kecamatan Kebayoran Baru Kota Administrasi Jakarta Selatan - Muhammad Helmi Zein (Jurnal Inovasi Penelitian, 2021)
Jakarta has a relatively low number of settlements and the level of comfort index for residents of Jakarta is still at an average level. This is due to the lack of good public infrastructure. The Provincial Government of DKI Jakarta has made a program for Handling Infrastructure and Public Facilities (PPSU) in order to accelerate the functioning of locations / infrastructures and assets of public facilities as well as damaged, dirty or unsuitable utilization. The Program launched in order to optimize services to the community. The purpose of this research is to explain how the implementation of Public Infrastructure and Management Handling Program (PPSU) in Melawai sub-district, explains the factors that influence the implementation and analyze strategies in improving the program. This study uses descriptive qualitative research method with an inductive approach. Data collection comes from observations, interviews and documentation. Data analysis techniques in this study use data reduction, data presentation and conclusion drawing and finding strategies by SWOT analysis. Based on the result, founded by the author, the implementation of PPSU in Melawai sub-district has not been running optimally. As has not yet been seen to be maximum are the support of community participation to engage in environmental cleaning up activities, the frequent accumulation of rubbish heaps, dirty sewers and illegal graffiti have not been handled. The success of the program have not been achieved because of influenced by the low performance of PPSU officers in terms of work motivation and less discipline. The author recommends a strategy by periodically evaluating the performance of PPSU officers and improving the operational (monitoring, coaching and supervising) operations of PPSU officers intensively and sustainably.